Surgical Repair of the Postoperative Lung Hernia by Combining Mesh Interposition and Chest Wall Stabilization by Using Synthes Plates: A Novel Technique - Dragan Subotic; Mark Wiese; Aljaz Hojski; Didier Lardinois (Case Reports in Surgery)
Several technical points for postoperative lung hernia repair are still not fully elucidated. We present an original technical solution to deal with this complication. In a 68-year-old female, the lung hernia was confirmed 5 months after the partial left-sided chest wall and scapula angle resection with primary Mersilene mesh reconstruction for elastofibroma. The patient refused the proposed surgical correction, being only slightly limited in daily activities. The symptoms persisted under analgetic therapy till the moment when patient’s daily activities became critically limited, 22 months after surgery. The repeated chest CT showed a slight increase in hernia size with no signs of tumour recurrence, so that reoperation was planned. After the exposure of the mesh region, a lung protrusion (4×3 cm) along the anterolateral edge of the mesh was confirmed. By careful dissection, the mesh was separated from a firmly adherent lung and removed. After adhaesiolysis and complete lung liberation, a wedge resection of the afunctional lung tissue of the lingula was done, just in the region of contact with the mesh. After the chest tube insertion, the chest wall defect was reconstructed by using a Mersilene mesh, and the final chest wall stabilization was done by the fixation of two Synthes plates (DePuy Synthes J&J) over the 5th and 6th ribs. The postoperative course was uneventful. One year after the operation, the patient was in good general condition, without the need for analgesics. To the best of our knowledge, the described technique is the original way of dealing with postoperative lung hernia. We find it efficient as a prevention of potential serious hernia-related complications.